SISTEM INFORMASI LOKASI WISATA CANDI DI DAERAH ISTIMEWA YOGYAKARTA BERBASIS GEOGRAPHIC INFORMATION SYSTEM (GIS) - ., Zuliyanto; Hamzah, Amir; ., Suraya (Jurnal Script, 2014)
ABSTRACTThe selected range of data and information regarding an overview of State Pronvenced DIY, with the role of technology that began to grow very fast, therefore the development of the area started in order to advance his country in the field of tourism location information. Then the Government of Yogyakarta is attempting to provide service to the community in order to more easily get a tour of the temple which location information is really needed. This will be discussed in writing regarding the creation of information system of tourist locations in GIS-based DIY Temple. Needed in the design of this system, there are a variety of data. As for the supporting tools in use, namely php and other code editor using notepad, designing databases using MySQL. With the application of this system resulted in a tourist location information system Temple in YOGYAKARTA-based on Geographic Information System (GIS). So it can be used by the authorities in particular, and can be utilized by indigenous peoples in General. Tour the temple location information system based on Geographic Information System (GIS) greatly facilitate the public to obtain the required information. The existence of this information system, the development of means of information area in the province of DIY can be realized.Keywords: System, information, location, archaeological sights, GIS, Notepad